Effects of Lipoxin A4 Pretreatment on Cognitive Function of Aged Rats after Global Cerebral Ischemia Reperfusion - Wu, Hui-sheng; Guo, Pei-pei; Jin, Zhao; Li, Xin-yi; Yang, Xin; Ke, Jan-juan; Wang, Yan-lin; Feng, Xiao-bo (Current medical science, 2018)
Summary The aim of the present study was to investigate the effect of lipoxin A4 (LXA4) pretreatment on cognitive function of aged rats after global cerebral ischemia reperfusion, and to explore its possible mechanism. Thirty-six aged male Sprague-Dawley rats were randomly divided into three groups ( n =2 each): sham-operation group (S group), global cerebral ischemia reperfusion group (I/R group) and LXA4-pretreatment group (L group). The rat model of global cerebral ischemia reperfüsion was established by occlusion of the bilateral common carotid artery with hypotension. The cognitive function of rats was determined by a step-down type passive avoidance test and Morris Water Maze test on the third day after reperfUsion. Rats were sacrificed after Water Maze test and the pathological changes of hippocampal CAI region were observed and the related inflammatory mediators were determined. As compared with S group, the escape latency in I/R group was prolonged from the first day to the fifth day, while that in L group was prolonged from the first day to the third day. The retention time in I/R group and L group in the first quadrant was shortened. The reaction time, frequency of reaction mistake and frequency of escape mistake in I/R group increased, and the latent period shortened. The frequency of escape mistake in L group increased, and the damage in the hippocampal CAI region of I/R group and L group was obvious. The levels of S-100β, TNP-α, IL-lβ, IL-10 and NF-κB in I/R group and L group increased. As compared with I/R group, the escape latency in L group was shortened from the first day to the fifth day, and the retention time in the first quadrant prolonged. The reaction time, frequency of reaction mistake and frequency of escape mistake in L group decreased, and the latent period prolonged. The damage in the hippocampal CAI region of L group was alleviated as well. The levels of S-100β, TNP-α, IL-lβ and NF-κB in L group decreased, and those of IL-10 increased. It can be concluded that LXA4 pretreatment can improve the cognitive function in aged rats after global cerebral ischemia reperfusion probably by inhibiting the inflammatory reaction.